EFFORTS TO IMPROVE STUDENTS LEARNING OUTCOMES ON ECLIPSE MATERIALS USING THE DEMONSTRATION METHOD IN CLASS VI - Rosideh Rosideh; Agung Setyawan (Citra Dharma Cindekia, 2022)
The science learning outcomes of sixth graders at SDN Dlemer in understanding solar and lunar eclipses are still low. This is caused by teachers who only use the lecture method so that learning becomes ineffective. To improve student learning outcomes on the material of solar and lunar eclipses, it is necessary to have a variety of learning methods, one of which is the demonstration method. Therefore, this study aims to determine whether the demonstration method can improve the learning outcomes of sixth grade students at SDN Dlemer. This research is in the form of classroom action research which is carried out in two cycles. Collecting data using interview, observation, test, and documentation techniques. The results of this study indicate that the learning outcomes of students in science subjects regarding solar and lunar eclipses have increased. In the first cycle the average value of the class was 54.37 and the remaining number of students who successfully completed it were 6 students or 37.5%. In the second cycle the average value of the class increased to 80.25 with the number of students who successfully completed 14 students or 86.5%. Based on these results, it can be concluded that the use of the demonstration method can improve student learning outcomes.